Privacy Preserving Public Auditing with Data Storage Security in Cloud Computing : An Overview - Manimegalai, R; Priyadharshini, A (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is an Internet-based computing pattern through which shared resources are provided to devices on demand. In order to provide safe and secure operation propose a hierarchical attribute based access control scheme by extending cipher text-policy attribute-based encryption (CP-ABE) with a hierarchical structure of multi authorities and exploiting attribute-based signature (ABS). The proposed scheme not only achieves scalability due to its hierarchical structure, but also inherits ﬁne-grained access control with authentication in supporting write privilege on outsourced data in cloud computing. In addition, we decouple the task of policy management from security enforcement by using the extensible access control markup language (XACML) framework. Extensive analysis shows that our scheme is both efficient and scalable in dealing with access control for out- sourced data in cloud computing.